Custom-made semi-joint prosthesis replacement combined ligament advanced reinforcement system (LARS) ligament reconstruction for the limb salvage surgery of malignant tumors in the distal femur in skeletal immature children - Zan, Pengfei; Shen, Jiakang; Liu, Kaiyuan; Wang, Hongsheng; Cai, Zhengdong; Ma, Xiaojun; Sun, Wei (Frontiers in Pediatrics, 2023)
Purpose To explore the application of Custom-made Semi-joint prosthesis replacement combined with Ligament Advanced Reinforcement System (LARS) ligament reconstruction for the limb salvage surgery (LSS) of malignant tumors in the distal femur and provide selections for the LSS of malignant tumors in skeletal immature children. Methods A total of 8 children with malignant tumors in the distal femur who underwent Custom-made Semi-joint prosthesis replacement combined LARS ligament reconstruction for LSS from January, 2018 until December, 2019 in our bone and soft tissue tumor center were retrospectively recruited. The prosthesis related complications, oncological prognosis and knee function were observed, and the surgical efficacy was comprehensively evaluated. Results The average follow-up time was 36.6 months (30–50 months). The average osteotomy length was 13.2 cm (8–20 cm) according to the preoperative imaging results and the length of the customized prosthesis. Two years after operation, the average MSTS-93 score was 24.4 (16–29) which indicated good limb functions. The range of motion of the knee was 0°–120°, with an maximum average of 100°. At last follow-up, the average height of the children increased by 8.4 cm (6–13 cm), and the average limb shortening was 2.7 cm (1.8–4.6 cm). One patient had wound complications in the early postoperative period, wound scab fell off to form superficial ulcer, in whom debridement and suturing were performed. One patient developed hematogenous disseminated prosthesis infection 2 years after surgery, and the prosthesis is now in situ with anti-infection treatment. One patient developed pulmonary metastasis during follow-up, and received chemotherapy and targeted therapy with lesion well controlled. At the last follow-up, there was no local tumor recurrence or prosthesis loosening. Conclusion Under the premise of appropriate case selection, customized semi-joint prosthesis replacement combined with LARS ligament reconstruction provides a new option for LSS in children with distal femur malignant tumors. LARS ligament reconstruction ensures the stability and range of motion of the knee joint, which maximally preserves the epiphysis of the tibia side and the growth function of the tibia side, reduces the complications of limb length inequality in the long term and creates conditions for limb lengthening or total joint replacement in adults.